2017
DOI: 10.1016/j.molp.2016.06.016
|View full text |Cite
|
Sign up to set email alerts
|

Distant eQTLs and Non-coding Sequences Play Critical Roles in Regulating Gene Expression and Quantitative Trait Variation in Maize

Abstract: A detailed understanding of genetic architecture of mRNA expression by millions of genetic variants is important for studying quantitative trait variation. In this study, we identified 1.25M SNPs with a minor allele frequency greater than 0.05 by combining reduced genome sequencing (GBS), high-density array technologies (600K), and previous deep RNA-sequencing data from 368 diverse inbred lines of maize. The balanced allelic frequencies and distributions in a relatively large and diverse natural panel helped t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
162
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 153 publications
(168 citation statements)
references
References 69 publications
6
162
0
Order By: Relevance
“…NALT upregulation was associated with NOTCH1, and increased NALT expression dramatically promoted cell proliferation in cell lines as shown by the CCK8 assay and EDU stain (Wang et al ., ). Furthermore, a study on maize showed that non‐CDS play critical roles in regulating gene expression (Liu et al ., ). In Medicago truncatula , some lncRNAs associated with osmotic and salt stress were identified; these lncRNAs were co‐expressed with protein‐coding RNAs within 100 kb of their location.…”
Section: Discussionmentioning
confidence: 97%
“…NALT upregulation was associated with NOTCH1, and increased NALT expression dramatically promoted cell proliferation in cell lines as shown by the CCK8 assay and EDU stain (Wang et al ., ). Furthermore, a study on maize showed that non‐CDS play critical roles in regulating gene expression (Liu et al ., ). In Medicago truncatula , some lncRNAs associated with osmotic and salt stress were identified; these lncRNAs were co‐expressed with protein‐coding RNAs within 100 kb of their location.…”
Section: Discussionmentioning
confidence: 97%
“…Investigation of eQTNs provides insights into the gene expression effects of candidate loci and helps to unravel the relationship between genotypes and phenotypes (Westra and Franke, ). In our studies, the eQTNs identified for 42 expressed lignin biosynthetic genes were more abundant in noncoding regions than those in coding sequences (82.93% vs. 17.07%) (Figure S8), highlighting the regulatory roles of noncoding sequences for quantitative traits (Li et al ., b; Liu et al ., ). Additionally, trans ‐eQTNs are more frequent in the genome, which indicates that genes are largely regulated by trans ‐eQTNs (Drost et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Epistasis is a critical component of genetic effect for the phenotypes and is important for our understanding of heritability (Xu and Jia, ). The eQTNs allow for resolution down to the single‐nucleotide level by determining the function of alleles in phenotypes (Liu et al ., ). LncRNAs, miRNAs and TFs have an important and broad‐spectrum impact on the lignin biosynthesis pathway, which affects the genetic architecture of tree growth and wood formation.…”
Section: Discussionmentioning
confidence: 97%
“…In a recent study, an automated noninvasive phenotyping method was also used to monitor the plant sizes of 252 diverse maize inbred lines by focusing on biomass at 11 different developmental time points, and 12 main-effect marker-trait associations were identified (Muraya et al, 2017). Association mapping in maize is a very powerful tool to identify genes with high resolution if millions of molecular markers and a large population size are used Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%